Negr1-Derived Peptides Trigger ALK Degradation and Halt Neuroblastoma Progression In Vitro and In Vivo - Francesca Pischedda; Alessia Ghirelli; Vasvi Tripathi; Giovanni Piccoli (MDPI AG, 2023)
Neuroblastoma is among the most common childhood cancers. Neuroblastoma in advanced stages is one of the most intractable pediatric cancers, notwithstanding the recent therapeutic advances. ALK mutations are among the leading cause of hereditary neuroblastoma and account for more than 14% of the somatically acquired alterations. ALK kinase activity is currently one of the main targets for pharmacological strategies. However, evidence from ALK fusion-positive lung cancer studies has shown that resistance to ALK inhibition arises during the therapy, causing a relapse within several years. IgLONs are membrane-bound proteins involved in cell-to-cell adhesion. The expression of the IgLON family results altered in different cancers. We found that the IgLON member Negr1 is downregulated in neuroblastoma. The ectopic overexpression of Negr1 impairs neuroblastoma growth in vitro and in vivo. Negr1 exists as a GPI-anchored membrane-bound protein and as a soluble protein released upon metalloprotease cleavage. We generated and characterized a panel of Negr1-derived peptides. The treatment with Negr1 protein and derived peptides induce ALK downregulation and halt neuroblastoma progression in vitro and in vivo.